Functionalized polyhydroxyalkanoate nano-beads as a stable biocatalyst for cost-effective production of the rare sugar d-allulose. (October 2019) - Ran, Ganqiao; Tan, Dan; Zhao, Jiping; Fan, Fan; Zhang, Qiang; Wu, Xingjuan; Fan, Peiyao; Fang, Xinlei; Lu, Xiaoyun
Graphical abstract: Highlight: One step production of immobilized DTE in recombinant endotoxin-free ClearColi . The yield of immobilized DTE was as much as 54 ± 3.6 wt% of cell dry weight. Immobilized DTE retains considerable specific activity and high conversion rate. The operational stability was remarkably improved after immobilization. No obvious loss of their initial activity after 8 recycles. Abstract: d -Allulose is a promising low-calorie sweetener especially for diabetes and obesity patients. The functionalized polyhydroxyalkanoate (PHA) nano-beads decorated withd -tagatose 3-epimerase (DTE) was produced in recombinant endotoxin-free ClearColi, whereby the expression, purification, and immobilization of the active DTE were efficiently combined into one step. The immobilized DTE exhibited remarkable enzyme activity of 649.3 U/g beads and extremely high stability at a harsh working condition (pH 7.0–8.0, 65 °C). When DTE-PHA beads were subjected to enzymatic synthesis ofd -allulose, a maximum conversion rate of 33% can be achieved at pH 7.0 and 65 °C for 3 h, and DTE-PHA beads retained about 80% of its initial activity after 8 continuous cycles. Moreover, thed -allulose/d -fructose binary mixture can be simply separated by a single cation exchange resin-equipped chromatography. Taken together, DTE-PHA beads are promising and robust nano-biocatalysts that will remarkably simplify the production procedures ofd -allulose, contributing to its cost-effective production.